2021
DOI: 10.3390/su13042315
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Value at Risk Goal Function in Bi-Level Portfolio Problem for Financial Sustainability

Abstract: The mean-variance (MV) portfolio optimization targets higher return for investment period despite the unknown stochastic behavior of the future asset returns. That is why a risk is explicitly considering, quantified by algebraic characteristics of volatilities and co-variances. A new probabilistic definition of portfolio risk is the Value at Risk (VaR). The paper makes explicit inclusion and minimization of VaR as a quantitative measure of financial sustainability of a portfolio problem. Thus, the portfolio we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Furthermore, ref. [4] concluded that two main criteria should be used as parameters for quantifying portfolio sustainability: portfolio return and portfolio risk, with preference towards risk [5] using long-term memory (LSTM) networks [6] that are ideal for learning classification, time series processing and prediction problems, where important events are separated by indefinite time and boundary time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ref. [4] concluded that two main criteria should be used as parameters for quantifying portfolio sustainability: portfolio return and portfolio risk, with preference towards risk [5] using long-term memory (LSTM) networks [6] that are ideal for learning classification, time series processing and prediction problems, where important events are separated by indefinite time and boundary time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…While considering the enormous benefits that investment can bring, business should be prepared for the potential risks that come with it. During the capital investment process, rational investors will consider how to allocate a certain amount of capital to thousands of risky securities in order to spread the risk as widely as possible and obtain the greatest benefit [ 2 ]. The securities market, on the other hand, is a financial trading market where risks and interests coexist.…”
Section: Introductionmentioning
confidence: 99%